Distribution of Gastropods in Mangrove Forest Area of Segara Anakan Cilacap - Teguh Sugiarto; Chrisna Adhi Suryono; Jusup Suprijanto (Masyarakat Moluska Indonesia, 2021)
This study aims to determine the distribution and diversity of gastropods at two locations with different levels of sedimentation in the mangrove forests of Segara Anakan Cilacap. This research was conducted during May-August 2002 in the mangrove forest area of Segara Anakan Cilacap. Analysis and identification of samples were carried out at the Laboratory of Marine Geology and Chemistry, Department of Marine Sciences, Diponegoro University, Awur Bay, Jepara. A preliminary survey was conducted to determine the research location, namely Klaces with high sedimentation rates and natural Sapuregel or areas with low sedimentation rates. At each research location 3 stations (I, II, and III) were determined, each of which was a transect line along 500 m. Each station has 3 sub stations, namely A (on the river bank), B (250 mr), and C (500 m) from the starting point. At each sub station there are two plots of 5m x 5m as a place for taking samples. The results showed that in the mangrove forests of Segara Anakan Cilacap, 29 species from 10 gastropod families were found. Cerithidea obtusa and Neritina violacea dominate the Klaces location with an average abundance of 14.04 individuals / m2 and 8.17 individuals / m2, respectively. Sapuregel was dominated by Nerita lineata with an average abundance of 1.77 individuals / m2. The Index of Diversity and Evenness in Sapuregel (2.48 and 0.61) was higher than the Klaces (1.73 and 0.42). Meanwhile, the Dominance Index in Klaces (0.46) is greater than that of Sapuregel (0.24). The community similarity between Klaces and Sapuregel is high, namely 65.12%.